3302 Student Leadership Training effects on team dynamics and collaborative work in high-pressure, interprofessional team environments. (27th March 2019) - Tumilty, Emma; Chao, Celia; Aronson, Judith F.; Hellmich, Mark R.
Abstract : OBJECTIVES/SPECIFIC AIMS: We aimed to explore the impact of leadership training on student's abilities to work in interprofessional research teams successfully. The Translational Research Design and Interprofessional Skills Development Course (shortened, Interprofessional Research Design) brings together students from different disciplines (science & medicine) and education tracks (PhD, MD, MD/PhD training) in a seven-week course to learn interprofessional collaborative skills and leadership styles that support success in translational research environments, while undertaking a research grant writing project. Part of the course involves a two-day leadership training workshop (12 hours) with the goal of understanding leadership styles and how to develop productive working relationships with team members to help students work more effectively in high-performance, interprofessional team environments. The course incorporates personality testing to develop self-awareness, with various exercises meant to build empathy, as well as knowledge of project management and effective leadership. METHODS/STUDY POPULATION: Nine teams of 32 students (23 MD; 9 Ph.D.) who took part in the Interprofessional Research Design course in 2017 and 2018 were required to write a reflective essay at the end of the course. We used an inductive thematic analysis to evaluate the essays. Reflective essays were coded openly by one study member. Codes were rationalized; then codes were collaboratively developed into themes by the study authors. We identified issues of integration between student groups that functioned well together and those that did not. Reflective writing responses were grouped into overall positive experiences and negative experiences. RESULTS/ANTICIPATED RESULTS: Seven of the nine teams collectively described their experiences positively. Themes related to positive team experience were "empathizing with group members", "sophisticated communication" and "collaborative workflow/styles." We found that those who had a positive experience utilized knowledge and skills learned during leadership training to better understand and communicate with their teammates leading to a more collaborative and dynamic workflow. These groups had higher degrees of communication both between their task assignments and within task completion periods. They also showed more awareness of others' needs in work and communication styles. For those that had a negative experience, themes were related to "basic communication", "poor integration" and "theory-practice gap of leadership training." Those who struggled showed much less in- and between-task communication and showed an inability to address the personal needs of other members in communication and workflow (while still often being able to identify them). DISCUSSION/SIGNIFICANCE OF IMPACT: These findings demonstrate the usefulness of leadership training that facilitates student self-awareness and empathy, as well as effective communication, leading to collaborative high-functioning interprofessional teams. Further work incorporating conflict management and exercises to overcome the theory/practice gap of leadership and teamwork training are recommended.